Communication Strategy of The Prevention And Community Empowerment Team of BNN Tangerang City in The Drug-Free Village Program - Riswandi, Rafa Wahyu; Yuniani, Hani; Lancia, Ferari (Manunggal Halim Jaya, 2025)
The rate of drug abuse in Indonesia continues to increase every year, and Tangerang City, Indonesia, is one of the areas experiencing a rise in drug-related cases annually. Therefore, through the Drug-Free Village Program, BNN Tangerang City strives to reduce the level of drug abuse in the area. This study aims to explain the communication strategy used by the Prevention and Community Empowerment Team of BNN Tangerang City in the Drug-Free Village Program. The theories used in this research are the Elaboration Likelihood Model (ELM) and communication planning. This study employs a descriptive qualitative method, with the research subject being the Prevention and Community Empowerment Team of BNN Tangerang City. The findings of this study conclude that the communication strategy used by the Prevention and Community Empowerment Team of BNN Tangerang City consists of ten stages of communication planning, starting with gathering data related to the program, determining program objectives, defining strategies, segmenting the audience, selecting channels, structuring messages, conducting management planning, organizing training, implementing the program, and finally, evaluating the program. According to the Prevention and Community Empowerment Team of BNN Tangerang City, implementing the Drug-Free Village Program has been quite effective in increasing community participation in preventing drug abuse. This is evidenced by the continued operation of P4GN activities in villages that have been designated as drug-free villages, even after the program has officially ended. However, improvements in strategy evaluation and development must continue to be made to create a more effective communication strategy.